Antimicrobial properties of composite film based polyvinyl alcohol/starch/nanocellulose from sugarcane bagasse coated with essential oil - Asem, Maimunah; Jimat, Dzun Noraini (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Food packaging functions to protect food from the environment and to prevent microbial contamination. Antimicrobial packaging is one application of active packaging and it one of the most promising active packaging developed among the researchers over the last decade. Antimicrobial food packaging incorporates antimicrobial compounds to the packaging material which functions to maintain the product safety, quality, and extension of shelf life. This study aims to explore the effects of coating essential oils (lemongrass, citronella, and peppermint) to the PVA/starch/nanocellulose composite film. Antibacterial activity test against Escherichia coli and Staphylocoocus aureus on films were carried out using agar diffusion method to select the best essential oils that can inhibit the bacteria. PVA/starch/nanocellulose film coated with lemongrass essential oil exhibited the largest inhibition zone for S. aureus bacteria. The obtained results reveal that the coating of essential oils leads to an enhancement of the composite film’s antimicrobial properties. These results indicate that the PVA/starch/nanocellulose composite film coated with essential oil is potential to be used as food packaging materials.